2021
DOI: 10.1007/s40429-021-00383-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Classification Considerations Related to Compulsive Sexual Behavior Disorder and Problematic Pornography Use

Abstract: Purpose of Review There are ongoing debates about specific features of compulsive sexual behavior disorder (CSBD) relating to classification and diagnoses. We aim to address current discussions relating to potential subtypes of CSBD, the aspect of compulsivity in CSBD, and the aspect of moral incongruence and CSBD. Recent Findings CSBD includes multiple specific sexual behaviors that might be related to specific psychological processes. Problematic pornogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Fourth, the frequency of sexual encounters did not differ between groups. CSBD patients, however, showed more frequent pornography consumption often observed in CSBD ( Antons et al., 2021 ). In addition, we found a correlation between VS activity during anticipation and pornography consumption measures.…”
Section: Limitationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Fourth, the frequency of sexual encounters did not differ between groups. CSBD patients, however, showed more frequent pornography consumption often observed in CSBD ( Antons et al., 2021 ). In addition, we found a correlation between VS activity during anticipation and pornography consumption measures.…”
Section: Limitationsmentioning
confidence: 90%
“…While both mechanisms may contribute, they cannot be disentangled in this study. However, it is well-known that depression and CSBD are highly correlated ( Antons et al., 2021 ), thus, our study cohort represented an ecologically valid clinical sample of patients with CSBD. Fourth, the frequency of sexual encounters did not differ between groups.…”
Section: Limitationsmentioning
confidence: 99%
“…The Pornography Problems due to Moral Incongruence model (PPMI; Grubbs, Perry, Wilt, & Reid, 2019 ) was developed to explain the contribution of both moral conflict and behavioral dysregulation to the development of problematic pornography use (PPU). In the present paper, PPU is conceptualized as a manifestation of CSB involving use of pornography that leads to distress and impairment ( Antons & Brand, 2021 ). The PPMI asserts that self-perceived PPU may arise from moral incongruence (MI), or a conflict between a person's moral or religious disapproval of pornography and their pornography use behavior.…”
Section: The Pornography Problems Due To Moral Incongruence Modelmentioning
confidence: 99%
“…Individuals suffering from CSBD experience significant impairment or distress due to failure to control sexual thoughts and impulses resulting in repetitive sexual behavior ( WHO, 2018 ). CSBD has several behavioral manifestations, including paid sexual services, pornography use, masturbation, and partnered sexual activities ( Antons & Brand, 2021 ).…”
mentioning
confidence: 99%
“…PPU can be considered as a subtype of compulsive sexual behavior disorder (CSBD; [6]), and research has shown that the majority of patients seeking treatment for CSBD report PPU as their primary problematic sexual behavior [7]. Therefore, current opinions view PPU as a subtype of this construct [8,9] and also assume that many patients presenting with CSBD will show PPU as their primary problematic sexual behavior. Since the inclusion of CSBD in the International Classification of Disease (ICD-11; [10]) in 2019, CSBD Topical Collection on Sex Addiction.…”
Section: Introductionmentioning
confidence: 99%